The Management Natural and Innovation Agriculture : A case study of a Self Sufficiency Economy Outdoor Center at Ban Nong Bua Thong Tumbon Khuanwan Muang Nongkhai Province - Chansri, Kornkrit (Journal for Developing the Social and Community, 2021)
The purposes of this research were to study the innovational agriculture resource management and to study the problems and solutions the innovational agriculture resource Management of a sufficiency economy outdoor center at Ban Nong Bua Thong, Tumbon Khuanwan Muang District, Nong Khai Province. It was a qualitative research. The sample consisted of 26 people in Ban Nong Bua Thong,Tumbon Khuanwan,Muang District ,Nong Khai Province, chosen by the purposive random sampling. The instrument used in this research was interview form. The data were statistically analyzed with ATLAS.ti. program. The results of this research show that 1) The Innovational Agriculture Resource Management : A case study of a sufficiency economy outdoor center at Ban Bua Thong,Tumbob Khuanwan, Muang District, Nong Khai Province. The management is done by these processes. 1.1) Planning the strategies, vision, mission, objective of this center in 10 years period (2012-2022) by 30 per cent for reservoir, 30 per cent for rice farming, 30 percent for cattle and 10 per cent for housing and study from the successful sufficiency economy area. 1.2) Setting structure of center and diung fokkow the action plans. 1.3) Managing the personnel section sffectively. 1.4) Controlling the process and managing resources; man, budget,material and land management. 1.5) Having a good connection between local officers and private sections. 1.6) Having a good budget management. And 1.7) Reporting the action plans systematically. 2) The problems of this center are basic structural public utility, various agricultural products, online media, lack of experts, connecting with local officers and private sections and budget problems in providing material for training officers. The solutions of those problems are 1) Setting a project to develop the center to gain a budget from Nong Khai municipality office. 2) Setting a project with other organization in Nong Khai such as Khon Khan University Nong Khai Campus or Nong Khai Agricultural Office to train the officers in this center to be the experts. 3) Setting a project to take the budget from related offices in NongKhai.